Disseminated Tuberculosis Causing Pancytopaenia in an Indian Boy - Roy, A; Chaudhuri, J; Kumar, K; Mukhopadhyay, D (Journal of Nepal Paediatric Society, 2013)
Tuberculosis still remains a major public health problem, particularly in developing countries. We report 11 year old Indian boy who presented with low grade fever, weight loss, hepatomegaly, ascites and petechial spots for past 6 weeks associated with pancytopaenia. Subsequently, bone marrow biopsy from the iliac crest revealed an epithelioid cell granuloma with hypercellularity. This is a rare presentation where disseminated tuberculosis presented as pancytopaenia. DOI: http://dx.doi.org/10.3126/jnps.v33i1.7577 J Nepal Paediatr Soc. 2013;33(1):52-54